2022
DOI: 10.1002/advs.202204017
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Imidazolium 1D Perovskite Capping Layer Stabilized 3D Perovskite Films for Efficient Solar Modules

Abstract: Although the perovskite solar cells have been developed rapidly, the industrialization of perovskite photovoltaics is still facing challenges, especially considering their stability issues. Here, the new type of benzimidazolium salt, N,N′‐dialkylbenzimidazolium iodide, is proposed and functionalized to convert the three‐dimensional (3D) FACs‐perovskite films into one‐dimensional (1D) capping layer topped 1D/3D structure either in individual device or module levels. This conformal interface modulation demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The increased CPD value of 2D-3D film suggested that the Fermi level of perovskites' surface became higher after DEAI passivation, which would enhance the V oc . [23,24] To assess the defect states in both pristine and 2D-3D perovskite films, we employ the space-charge-limited-current method through the fabrication of hole-only devices. First, the dark J-V curves of the hole-only devices, with structures of ITO/MeO-2PACz/perovskite/Spiro/Ag and ITO/MeO-2PACz/perovskite/ DEAI/Spiro/Ag, were measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased CPD value of 2D-3D film suggested that the Fermi level of perovskites' surface became higher after DEAI passivation, which would enhance the V oc . [23,24] To assess the defect states in both pristine and 2D-3D perovskite films, we employ the space-charge-limited-current method through the fabrication of hole-only devices. First, the dark J-V curves of the hole-only devices, with structures of ITO/MeO-2PACz/perovskite/Spiro/Ag and ITO/MeO-2PACz/perovskite/ DEAI/Spiro/Ag, were measured.…”
Section: Resultsmentioning
confidence: 99%
“…The increased CPD value of 2D–3D film suggested that the Fermi level of perovskites’ surface became higher after DEAI passivation, which would enhance the V oc . [ 23,24 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the 1D perovskite also acts as a fixed ion to enhance the stability of the device. [ 116 ] The PCE of the 1D–3D PSC synthesized by Zhan et al. was 21.17%, and the efficiency improvement was mainly due to the passivation of defects and the reduction of the activation energy of ion migration after the formation of heterojunctions (as shown in Figure 11 ).…”
Section: Ld–3d Solar Cell Propertiesmentioning
confidence: 99%
“…To solve these issues, some efforts have been made to not only suppress the phase-segregation issue of the WBG perovskite, 30,31 but also decrease nonradiative recombination loss by means of composition regulation, [32][33][34] crystallinity control 35 and surface/interface modication. 36,37 Among them, molecule passivation has drawn a lot of attention for the potential to enhance stability due to simple post-treatment and strong chemical passivation during the assembly processes, including small molecules, [38][39][40] imidazolium, 41 thiazolium halide, 42 and other ammonium salts. [43][44][45] Although they can improve the WBG perovskite quality and coordinate unsaturated Pb 2+ ions to repair defect sites, these protocols are not referred to the fabrication of inverted WBG solar modules, and the molecular chemical structures further need to be explored to enhance the performance of WBG PSCs.…”
Section: Introductionmentioning
confidence: 99%